KAJIAN STILISTIKA DAN NILAI PENDIDIKAN KUMPULAN GEGURITAN AJA NGANTI KAMANUNGSAN KARYA SUKSMAWAN YANT MUJIYANTO SERTA RELEVANSINYA SEBAGAI MATERI AJAR BAHASA JAWA DI SEKOLAH MENENGAH ATAS KELAS XII - Yulianto, Ari Tejo; Suyitno, Suyitno; Rahmat, Rahmat (Universitas Sebelas Maret, 2018)
This research aims to describe and explain (1) the stylistic aspect in geguritan Aja Nganti Kamanungsan by Suksmawan Yant Mujiyanto; (2) the educational value in geguritan Aja Nganti Kamanungsan by Suksmawan Yant Mujiyanto (3) the relevance of collection geguritan Aja Ngani Kamanungsan by Suksmawan Yant Mujiyanto as Javanese teaching material for 12nd grade of Senior High School. This research is qualitative research. Therefore, the method of research is descriptive qualitative. The approach used is stylistic. The data and source data of this research are document and informants from 12th grade students, the document is in form of geguritan Aja Nganti Kamanungsan by Suksmawan Yant Mujiyanto and informants are 12th grade students, Javanese teacher, literature expert, and author. The data collection technique uses document/content analysis and interview. The sampling technique of research subject done with particular consideration called purposive sampling. The technique of data test validity in this research uses source and theory triangulation. Meanwhile, data analysis technique of this research uses interactive analysis technique. Based on the research result, geguritan collection Aja Nganti Kamanungsan by Suksmawan Yant Mujianto has some stylistic aspects and educational values which are applicable to Javanese teaching material for 12th grade of Senior High School. Stylistic aspects here are phoneme, diction, syntax, figurative language and imagery. As for educational values here namely religious education value, morale, and social. From the five stylistic aspects above, the phoneme especially for assonance has the highest domination in geguritan collection Aja Nganti Kamanungsan which is relevant as teaching material for 12th grade of Senior High School which is expected not only useful in the formal education, but also useful in the informal education like in the society by applying the educational values in daily lives.